Assessing The Impact of Rotational Angular Breathing on Lung Functions and Health-Related Quality of Life in Adolescent Idiopathic Scoliosis (International Journal of Physiotherapy, 2024)
Background: The Adolescent Idiopathic Scoliosis deformity manifests itself during the adolescent development spurt. On the other hand, adolescent therapy aims to lessen curve growth, thus reducing the likelihood of back discomfort, weakness, aberrant pulmonary function, and cosmetic diseases and improving quality of life. Schroth exercises (Rotational breathing exercises) consider the positioning of the entire body to establish a stable, corrected posture. The study aimed to determine the impact of adding rotational angular breathing exercises on the 1-year outcome of mild adolescent idiopathic scoliosis. The study's objectives were to assess the effect on daily living activities using short form 36, assess the effect on respiratory functions using pulmonary function test, and find out the difference in respiratory functions.Methods: Participants in the study were between the ages of 10 and 15 years (19 Male and 17 Female), diagnosed with a specific type of AIS, characterized by Cobb’s angle measurements less than 20° for curves in the thoracic region and less than 15° for curves in the thoracolumbar area. Cases of group 1 had undergone the specific breathing exercise protocol, i.e., Rotational angular breathing exercises; however, other groups followed conventional exercise therapy.Results: A significant finding of this study is that parameters related to quality of life significantly improved in groups (p